Acute and Short-Term Effects of Oral Feeding of Jujube Solution on Blood Platelets and its Morphological Indices in Response to a Circuit Resistance Exercise - Seyed Morteza Tayebi; Ayoub Saeidi; Ali Akbar Mahmoudi; Leila Gharahcholo; Lida Radmehr (The Society of Aging and Physical Activity (SAPA), 2015)
The present study investigated the acute and short-term effects of oral feeding of jujube solution on blood platelets and its morphological indices in response to circuit resistance exercise. Fourteen young male volunteer students were randomly divided into the placebo and jujube solution groups. All participants performed one circuit resistance exercise[9stations/nonstop, 30 seconds for each station, 3sets with a 3-minute active rest between sets, and an intensity of 75%with one repeat maximum]. In an acute supplementation protocol, participants received either a placebo or a jujube solution(0.5g/kgbody weight in 2.5cc of distilled water) an hour before testing. Blood samples were collected 60minutes before feeding, immediately after, and 2hours after the exercise. In the short-term supplementation protocol, participants received either placebos or jujube solutions for as long as 7days at certain times and in a double-blind manner. Blood samples were collected 30 minutes before, immediately after, and 2 hours after the exercise. Platelet counts(PLT), platelet distribution width(PDW), mean platelet volume(MPV), and platelet large cell rate(PLC-R) were measured with a hematology auto analyzer. The acute supplementation protocol showed that PLT increased in the placebo group in response to exercise and decreased during the recovery period; in the jujube solution group the alterations were insignificant(p=0.031). PDW,MPV, and PLC-R were not affected by supplementation type and did not change in response to exercise, but they decreased during the 2-hour recovery period(p<0.05). The short-term supplementation protocol showed that PLT,PDW,MPV and PLC-R were not affected by supplementation type and did not change in response to exercise(p<0.05), but all values except PLT(increased in response to exercise and during recovery [p<0.05]) decreased in the 2-hour recovery period(p<0.05). In conclusion, acute jujube solution supplementation could inhibit PLT in response to circuit resistance exercise; so, it can probably inhibit the negative effects of intensive circuit resistance exercise on platelet aggregation and activation.